2013
DOI: 10.1039/c3cc45308a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hydrothermal stability of zeolitic imidazolate frameworks

Abstract: The metal-organic framework ZIF-8, which undergoes hydrolysis under hydrothermal conditions, is endowed with high water-resistance after a shell-ligand-exchange-reaction. The stabilized ZIF-8 retains its structural characteristics with improved application performances in adsorption and membrane separation.Metal-organic frameworks (MOFs) or porous coordination polymers (PCPs) are an emerging class of nanoporous materials showing a wide range of potential applications, e.g. gas storage, molecular separation, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
201
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 260 publications
(217 citation statements)
references
References 30 publications
9
201
0
Order By: Relevance
“…4(c). This loss of crystallinity is most likely caused by hydrolysis between the ZIF-8 ligands and the ambient moisture, which accelerates the decomposition of the ZIF-8 structure [32]. The samples were fully decomposed after exposure to steam at temperatures greater than 400°C for 5 h. Accordingly, we concluded that ZIF-8 was least stable in the steam atmosphere compared to the other two atmospheres.…”
Section: Thermal Stability Testsmentioning
confidence: 82%
“…4(c). This loss of crystallinity is most likely caused by hydrolysis between the ZIF-8 ligands and the ambient moisture, which accelerates the decomposition of the ZIF-8 structure [32]. The samples were fully decomposed after exposure to steam at temperatures greater than 400°C for 5 h. Accordingly, we concluded that ZIF-8 was least stable in the steam atmosphere compared to the other two atmospheres.…”
Section: Thermal Stability Testsmentioning
confidence: 82%
“…This impurity should be a kind of crystals consisting of Hmim ligands and zinc ions. That is different from hydrolyzed product, ZnO, reported by Yang and co-workers [26]. More research on decoding the impurity crystal and how it is formed are still needed.…”
Section: Mechanistic Study Of Stability Of Zif-8 Structure In Aqueousmentioning
confidence: 92%
“…Caro and co-workers [5,8] used precursor solution with a deficient zinc to Hmim ratio (1:1.5) for ZIF-8 membrane preparation. However, in most studies synthesis of both ZIF-8 membrane and crystals was performed with excessive Hmim ligands in synthesis solution [3,6,7,[10][11][12]23,26,[29][30][31]. Though most studies did not report ZIF-8 yield in the synthesis, a ca.…”
Section: Dynamic Stability Of Zif-8 Membrane During Pure Water Pervapmentioning
confidence: 92%
See 2 more Smart Citations